2000
DOI: 10.1177/026565900001600201
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioural difficulties in children with language impairment

Abstract: This paper examines the secondary social and behavioural difficulties of a large cohort of children attending language units in England. In stage 1 of the study, 242 children with language impairments were assessed on a measure of peer competence, a behavioural measure, a cognitive measure and also using teacher opinion of emotional/behavioural status in school year 2 (age 6-7). A year later, 214 of the children were followed up at age 7-8 years. The group is examined as a whole and in terms of subgroups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 32 publications
1
25
0
3
Order By: Relevance
“…This is absolutely in line with previous work in the field showing that sociable behavior highly depends on language competence and is usually strongly impaired in children with SLI (Botting and Conti-Ramsden 2000;ContiRamsden and Botting 2004;St Clair et al 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is absolutely in line with previous work in the field showing that sociable behavior highly depends on language competence and is usually strongly impaired in children with SLI (Botting and Conti-Ramsden 2000;ContiRamsden and Botting 2004;St Clair et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that behavioral and emotional problems increased during childhood and school years (Botting and Conti-Ramsden 2000;Conti-Ramsden and Botting 2004), but decreased up to adulthood -even though emotional problems still remained above population norms (St Clair et al 2011). Social problems, however, constantly increased during the same period of time (Botting and Conti-Ramsden 2000;Conti-Ramsden and Botting 2004;St Clair et al 2011), being strongly and chronically associated to SLI. In another series of studies, Mok et al (2014) analysed the longitudinal trajectories of peer relations in children with specific language impairment.…”
Section: Introductionmentioning
confidence: 93%
“…Language gives children access to a richer base of self-regulatory strategies, through which they are better able to modify negative emotions, including anger and frustration. Previous work has shown that both expressive and receptive language abilities are related to the development of emotion regulation skills (e.g., Botting & Conti-Ramsden, 2000; Silva, Justin, McGee, & Williams, 1984). Baker and Cantwell (1987) proposed an explanation for this relationship, asserting that delays in language acquisition may underlie a child's emotional dysregulation as the child is increasingly pressured to conform to environmental demands that they are unable to fully understand, resulting in frustration and non-compliance.…”
Section: Emotion Regulation Capacitymentioning
confidence: 99%
“…Some studies provide evidence that nonverbal IQ represents an important independent predictor of children’s behavioral symptoms (Benasich et al, 1993; Elbro et al, 2011; Gualtieri et al, 1983; Law et al, 2009; Silva, Justin, McGee, & Williams, 1984). Other investigations reported that nonverbal IQ was not a significant contributor (Botting & Conti-Ramsden, 2000; St. Clair et al, 2011; Tirosh & Cohen, 1998; Wadman, Botting, Durkin, & Conti-Ramsden, 2011). Other factors besides nonverbal IQ introduce confounds.…”
Section: Introductionmentioning
confidence: 94%